2005
DOI: 10.1212/01.wnl.0000179178.37713.69
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet therapy contributes to acute deterioration of intracerebral hemorrhage

Abstract: Antiplatelet therapy seems to contribute to the acute clinical deterioration of intracerebral hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
6
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 25 publications
6
144
6
7
Order By: Relevance
“…With regard to antiplatelet pretreatment, clinical studies revealed much more controversial results (Wijman, 2009). Some authors reported a significant influence of antiplatelet pretreatment on hematoma growth and outcome (Naidech et al, 2009;Roquer et al, 2005;Saloheimo et al, 2006;Toyoda et al, 2005), whereas others did not (Foerch et al, 2006;Moussouttas et al, 2010;Sansing et al, 2009). Interestingly, adjusting for baseline factors such as premorbid disability and concomitant diseases seems to be a crucial factor (Foerch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to antiplatelet pretreatment, clinical studies revealed much more controversial results (Wijman, 2009). Some authors reported a significant influence of antiplatelet pretreatment on hematoma growth and outcome (Naidech et al, 2009;Roquer et al, 2005;Saloheimo et al, 2006;Toyoda et al, 2005), whereas others did not (Foerch et al, 2006;Moussouttas et al, 2010;Sansing et al, 2009). Interestingly, adjusting for baseline factors such as premorbid disability and concomitant diseases seems to be a crucial factor (Foerch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, observational studies have indicated that previous use of platelet inhibitors in ICH is associated with higher mortality rates (Roquer et al, 2005;Saloheimo et al, 2006). Furthermore, reduced platelet activity may also be related to an increased early hematoma growth and a worse functional outcome at 3 months (Naidech et al, 2009;Toyoda et al, 2005). In contrast, several investigations have failed to identify the previous usage of antiplatelet agents as an independent risk factor of hematoma expansion and functional outcome in patients with ICH (Foerch et al, 2006;Moussouttas et al, 2010;Sansing et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes in individuals on antiplatelet therapy with an ICH are variable according to the available literature [135][136][137][138][139]. The best evidence includes a post-hoc analysis of the placebo arm of the CHANT study, which included 70 patients who were on antiplatelet therapy at onset of their ICH.…”
Section: Management Of Ich In Patients On Concurrent Antithrombotic Tmentioning
confidence: 99%
“…Several studies with various designs, sizes, and exclusion criteria have displayed conflicting results (Table 1) [7,9,10,[19][20][21][22][23]. While these studies typically report the use of any antiplatelets together in one research arm, aspirin users account for the vast majority of the subpopulation in all studies.…”
Section: Effects On Outcome In Spontaneous Ichmentioning
confidence: 99%
“…Some investigators have also reported that a prehospital antiplatelet regimen may be associated with hematoma expansion, an increased mortality rate, and a poor functional outcome [7][8][9][10]. As such, many institutions have established protocols to "reverse" the impairment of platelet aggregation caused by antiplatelet agents in patients presenting with ICH.…”
Section: Introductionmentioning
confidence: 99%